Induction of Avian β-Defensin 2 Is Possibly Mediated by the p38 MAPK Signal Pathway in Chicken Embryo Fibroblasts After Newcastle Disease Virus Infection - Liu, Chenggang; Jiang, Lei; Liu, Liangliang; Sun, Li; Zhao, Wenjun; Chen, Yuqiu; Qi, Tianming; Han, Zongxi; Shao, Yuhao; Liu, Shengwang; Ma, Deying (Frontiers in Microbiology, 2018)
The study was conducted to evaluate whether avian β-defensins (AvBDs) could be induced by Newcastle disease virus (NDV) infection, and to investigate the potential signaling pathway of AvBD2 induction in response to NDV infection as well. Firstly, mRNA expression of AvBDs (1–14) was evaluated in the chicken embryo fibroblasts (CEFs) cells infected with NDV strain F48E9 at 6, 12, 24, 36, and 48 hours post inoculation (hpi), respectively. The results demonstrated a significant induction of AvBD2 in CEFs elicited by the NDV strain. Then, we expressed and purified the AvBD2 proteins in both eukaryotic cells and prokaryotic cells. Of the two recombinant AvBD2 proteins, only the protein expressed in eukaryotic cells showed directly antiviral activity against NDV strain F48E9 in vitro. Ligands of toll-like receptors (TLRs) were chosen as alternatives to NDV for further studying signaling pathway of AvBD2 induction here, due to insufficient upregulation of AvBD2 expression elicited by NDV. We found that the mRNA expression of AvBD2 was highly upregulated by Pam3CSK4, FLA-ST and ODN-M362. Then, four inhibitors of signaling pathway, including inhibitors of JNK, ERK1/2, p38 MAPK, and NF-κB, were used in this study. Of the four inhibitors, only inhibition of the p38 MAPK signaling pathway significantly reduced AvBD2 expression after stimulation with Pam3CSK4, FLA-ST and ODN-M362, respectively. Taken together, these results revealed that AvBD2 play a pivotal role in host innate immunity response to NDV infection. The mRNA expression of AvBD2 might be regulated in a p38 MAPK-dependent manner.